The South Warwickshire NHS Care Records Service Demonstrator Project: lessons for the National Programme for IT. - Allwood, I; Holt, T (2005)
The NHS Care Records Service (CRS) is a major goal of the National Health Service (NHS) Modernisation Programme. It will provide for 24-hour access by clinicians to electronic patient records and the integration of information from previously separate databases, reducing the 'seams' between primary and secondary care, between out-of-hours and ordinary working hours, and ultimately between health and social care. Such integration is likely to affect not only individual patient care, but also public health including disease surveillance, and the monitoring of clinical activities including the achievement of clinical governance targets. The potential benefits for patients, practitioners and managers are numerous. However, the process raises issues over confidentiality, data protection and data quality. During 2003 a project was undertaken in South Warwickshire to develop an NHS CRS widely available to primary care clinicians in the region. This was part of a wider initiative funded by the NHS Connecting for Health (NHS CfH). Twenty-six out of 36 local practices took part, providing a combined database of 181,961 clinical records. All but one of the original objectives was achieved. Lessons were learned which could usefully inform the development of the CRS more generally in the NHS.